La cuestión del bien en el bioderecho: Una aproximación desde macintyre y dewan (2020)
Most disagreements of the practical order (androids, IVF; eugenics; preimplantation design; artificial intelligence; euthanasia and abortion) are generally due to previous disagreements of the theoretical order (understanding of good and human nature); conception of the person; foundations of dignity; hierarchy of principles). In other words, depending on the understanding of the good, biotechnological practices, applied ethics and their conceptualization and bio-legal regulation will vary in their limits and in their purposes. In this sense, the purpose of this article is, in accordance with the approaches of MacIntyre and Dewan, to show that the analogous understanding of the good, rooted in the ethics of the Aristotelian-Thomistic virtues, is the most successful option to guide practical reason, in general, and shed light on difficult cases of biolaw, in particular, in the face of the crisis of contemporary moral language.